Prevalence of Human Gastrointestinal Helminths among Residents of Wukari Metropolis, Taraba State, Nigeria - J. M., Ibrahim; H.I.J., Agere; M.C., Anongo; A.K., Mijah; I M., Usman; S.T.C, Brown (African Journal of Medicine, Surgery and Public Health Research, 2026)
This study investigated the prevalence of gastrointestinal helminths among residents of Wukari Metropolis, Taraba State, Nigeria. A total of 400 stool samples were collected from males and females aged 5–60 years across five wards (Bantaje, East, Puje, Hospital, and AVYI) using a cross-sectional descriptive design. Samples were examined microscopically by Kato-Katz, flotation, and sedimentation methods. Data were analyzed using SPSS v26, with chi-square tests applied at p < 0.05. Out of the 400 samples examined, 194 (48.5%) were positive for one or more helminths. Five species were identified: Ascaris lumbricoides (21.5%), Ancylostoma duodenale (14.25%), Taenia solium (7.25%), Trichuris trichiura (4.5%), and Strongyloides stercoralis (1.0%). Prevalence varied significantly by ward (χ² = 11.64, p = 0.03) and age group (χ² = 32.57, p = 0.0001), with the highest infection rates recorded in AVYI Ward (56%) and among individuals aged 10–19 years (72%). Females (51.9%) had a slightly higher prevalence than males (47.2%), though this difference was not statistically significant (χ² = 0.38, p = 0.54). The findings indicate that intestinal helminthiasis remains endemic in Wukari Metropolis, driven largely by poor sanitation, open defecation, and unsafe water sources. Integrated control measures involving periodic deworming, improved sanitation, access to clean water, and health education are recommended to curb transmission and improve public health outcomes.